Labor Market for Elderly People 2035 - Annette Scoppetta (Foresight and STI Governance)
Ageing of population is essential to most of European countries. This trend means both serious challenges as well as great potential for economic and social development. To bring this potential about it is necessary to provide equally high living standards for all age groups of population and first of all their employment. For this aim an Austrian interregional alliance “Territoriale Beshaftigungspakte” (territorial agreements on employment) has initiated in 2005 a Foresight study “Labor Market for Elderly People to 2035”. Common future visions were built, main trends related to the employment of elderly people were analyzed, and scenarios of labor market development to 2035 were developed. The project resulted in the complex strategy for strengthening positions of elderly people on labor market that integrated knowledge and experience of governing bodies of different levels, research organizations and independent experts.